Broom and Fraser's domestic animal behaviour and welfare - Broom, Donald M. (Wallingford, Oxfordshire ; Boston, MA : CAB International, 2021)
"Completely updated and revised with new information on sustainability, ethics, philosophy, human-animal interactions, data, tools and brain function and behaviour, the sixth edition of this best-selling book continues to provide veterinary and animal science students with a comprehensive yet approachable guide to animal behaviour and welfare"--
Introduction to ideas and measurement -- Fundamental topics -- Organization of behaviour -- Reproductive and social behaviour -- Early and parental behaviour -- Welfare topics -- Welfare of various animals.
Includes bibliographical references and index.
Keywords: Domestic animals -- Behavior; Animales domésticos -- Conducta; Mascotas -- Conducta; Pets -- Behavior; Animal welfare